Who killed the virtual case file? [case management software]. - Goldstein, H. (IEEE spectrum)
This paper discusses how the FBI's 170 million dollars Virtual Case File (VCF) IT project became one of the most highly publicized software failure in history. According to a report by the US Department of Justice's inspector general, VCF's failure may be attributed to several factors including poorly defined and slowly evolving design requirements, overly ambitious schedules, and the lack of a plan to guide hardware purchases, network deployments and software development for the bureau. The paper also includes interviews with people directly involved with the VCF to gain a better picture of an enterprise IT project that fell into the most basic traps of software development, from poor planning to bad communication.